2015
DOI: 10.1021/acs.joc.5b00378
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Chemical Amide Synthesis at Room Temperature: One More Step Toward Peptide Synthesis

Abstract: An efficient method has been developed for direct amide bond synthesis between carboxylic acids and amines via (2-(thiophen-2-ylmethyl)phenyl)boronic acid as a highly active bench-stable catalyst. This catalyst was found to be very effective at room temperature for a large range of substrates with slightly higher temperatures required for challenging ones. This methodology can be applied to aliphatic, α-hydroxyl, aromatic, and heteroaromatic acids as well as primary, secondary, heterocyclic, and even functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 64 publications
0
56
0
2
Order By: Relevance
“…8 This result was previously improved using our catalyst 5 (ee: 94%). 7 Interestingly, 9h afforded the desired amide 11 in 96% yield with the complete retention of enantiopurity (ee > 99%, Scheme 1). First attempts of coupling two protected α-amino acids at room temperature resulted in the total absence of conversion.…”
Section: Borinic Acid Catalysed Peptide Synthesismentioning
confidence: 99%
“…8 This result was previously improved using our catalyst 5 (ee: 94%). 7 Interestingly, 9h afforded the desired amide 11 in 96% yield with the complete retention of enantiopurity (ee > 99%, Scheme 1). First attempts of coupling two protected α-amino acids at room temperature resulted in the total absence of conversion.…”
Section: Borinic Acid Catalysed Peptide Synthesismentioning
confidence: 99%
“…Para a síntese dessa classe de compostos, diversas metodologias para formação de ligação C-N foram desenvolvidas, dentre essas destacam-se N-alquilação, 1,2 aminação redutiva com compostos carbonílicos, 3,4 N-acilação 5,6 e acoplamento cruzado C-N. 7,8 Entre os métodos modernos para construção de compostos nitrogenados complexos, a hidroaminação de compostos insaturados vem ganhando destaque e desperta interesse da comunidade científica. 9,10 Essa abordagem impacta na economia de átomos do processo, o que é benéfico do ponto de vista da química verde.…”
Section: Introductionunclassified
“…From the perspective of atom and step economy, achieving a direct Michael reaction of α,β-unsaturated carboxylic acids without the use of any activating templates is highly desirable. Despite strong synthetic utility, the direct Michael addition of α,β-unsaturated carboxylic acids has never been reported, except for an enzyme-catalyzed azaMichael addition 13,14) ; very few strategies have been exploited to catalytically activate the hydroxy group of carboxylic acids via transient covalent bond formation.By contrast, since the discovery by Yamamoto and Ishihara that electron-deficient arylboronic acids are efficient activators of carboxylic acids in direct amidation reactions, [15][16][17][18] 24,25) Hall reported that different types of arylboronic acids could be used for the cycloaddition of α,β-unsaturated carboxylic acids to dienes and 1,3-dipoles. 20,21) Recently, we also revealed that aminoarylboronic acid was the best catalyst for the intramolecular hetero-Michael addition of α,β-unsaturated carboxylic acids bearing sulfonamides or phenols.…”
mentioning
confidence: 99%
“…By contrast, since the discovery by Yamamoto and Ishihara that electron-deficient arylboronic acids are efficient activators of carboxylic acids in direct amidation reactions, [15][16][17][18] 24,25) Hall reported that different types of arylboronic acids could be used for the cycloaddition of α,β-unsaturated carboxylic acids to dienes and 1,3-dipoles. 20,21) Recently, we also revealed that aminoarylboronic acid was the best catalyst for the intramolecular hetero-Michael addition of α,β-unsaturated carboxylic acids bearing sulfonamides or phenols.…”
mentioning
confidence: 99%
See 1 more Smart Citation